(untitled) (المجلة الدولية للبحوث العلمية, 2023)
The study was conducted for a complicated lower humours fracture. This type of fracture is considered the most complex and difficult to heal, as it requires surgical intervention. This study investigates a child 4 years old with lower humours fracture into three pieces that was diagnosed by radiographic, she had surgery to fix by plates with the use of a casting and brace. After two months the plate and casting were removed, and then she started rehabilitating by physical therapy. Physiotherapy continued for three weeks, after which the patient regained full movement and practised his daily activities normally, and this confirms the importance and role of physiotherapy in such cases. Further studies are required to confirm these findings.